Cyclone Hudhud-eddy induced phytoplankton bloom in the northern Bay of Bengal using a coupled model. (September 2021) - Vidya, P.J.; Balaji, M.; Mani Murali, R
Highlights: Stratification inhibits eddy-driven upwelling in the northern Bay of Bengal. Eddy-cyclone interaction reduces the water column stability and initiates upwelling in the Bay of Bengal. Eddy-cyclone interaction induced phytoplankton bloom in the Bay of Bengal. Abstract: The present study explored the role of the pre-existing cyclonic eddy on the chlorophyll-a (Chl a ) bloom after a cyclone pass over the northern Bay of Bengal (BoB). We used a high-resolution (~9 km) Regional Ocean Modeling System (ROMS) coupled with an established Nutrient-Phytoplankton-Zooplankton-Detritus (NPZD) model. In the study, we have considered cyclone Hudhud (category-4), which passed over a cyclonic eddy in the BoB during 7–12 October 2014. Before the passage of cyclone Hudhud, strong stratification in the upper ocean inhibited eddy-driven upwelling of nutrients to the mixed layer and limited the phytoplankton production. However, when cyclone Hudhud interacted with the cyclonic eddy, which further reduced the water column stability (one order less) of the upper ocean and initiated the wind-driven upwelling. This mechanism resulted in the easy upwelling of cold nutrient-rich water to the mixed layer. A case study presented here demonstrates ocean–atmosphere (eddy-cyclone) interaction and its influence on the mixed layer Chl a production in the northern BoB. Our study showed that column integrated Chla value in the upper 100 m increased by 70% when cyclone Hudhud passed over a cyclonic eddy region in the BoB. The present study suggested that cyclonic eddy accompanied by cyclone Hudhud induced the Chl a bloom in the Northern Bay during the post-monsoon season of 2014.